Study on the influence of peripheral eye on over-excavation during mountain tunnel blasting construction - Zi-qiang Li; Gui-quan Ma; Ze-lin Zhou; Jia-shuai Zhang; Sheng-peng Pu; Zi-yi Zheng (Scientific Reports)
Abstract In this study, self-developed intelligent detection equipment was used to quickly detect the key parameters of peripheral eyes and scan the cross-section over-excavation based on the double-track tunnel project at Chongqing University Town. The correlation between the two was clarified using ANSYS/LS-DYNA finite element methods and then, the blasting drilling scheme was optimized. Three-dimensional imaging technology Integrated with high-precision laser scanning and an intelligent positioning system, is employed to acquire precise data regarding the excavation of the cross-section. The three-dimensional imaging technology intuitively represents the actual outline of the surrounding rock by creating a three-dimensional model of the tunnel excavation cross-section. The intelligent positioning system tracks the spatial coordinates of the blasthole in real time to ensure the accuracy of the position parameters of the peripheral eye. The results show that the positional deviation of the borehole in the perimeter eye can lead to significant over-excavation of the tunnel section, especially in the tunnel top and shoulder area. The field data show that when the average position deviation range of peripheral eyes is 17–23 cm, the over-excavation circumference of the tunnel measures 25.55–35.39 cm. The numerical simulation shows that the over-excavation caused by the spatial position deviation of the peripheral eye is approximately 2–3 times more than that caused by angular deviation, with average over-excavation in the top and shoulder areas of the tunnel reaching 45 cm and 18 cm, respectively. By implementing an optimized drilling strategy, the position deviation can be reduced to within 10 cm and the angular control can be improved, hence reducing the average over-excavation to 5 cm. The result serves as a benchmark for the further development of intelligent tunnel construction technology and the optimization of blasting construction under similar geological conditions.